Pengaruh Kecerdasan Emosional Dan Pemberdayaan Karyawan Terhadap Organizational Citizenship Behavior Dengan Motivasi Sebagai Variabel Mediasi Di Hotel Orchardz Ahmad Yani Pontianak - Pang, Ayrin Niagara; Budiono, Martha (Syntax Corporation, 2025)
This study aims to examine the influence of emotional intelligence and employee empowerment on Organizational Citizenship Behavior (OCB) with work motivation as a mediating variable among employees of Orchardz Hotel Ahmad Yani Pontianak. A quantitative approach was employed using a survey method by distributing questionnaires to hotel employees as respondents. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to test both direct and indirect relationships among variables. The findings indicate that emotional intelligence and employee empowerment have a positive and significant effect on OCB. Furthermore, motivation is proven to mediate the relationship between emotional intelligence, employee empowerment, and OCB. These results suggest that enhancing emotional regulation skills, providing greater empowerment, and strengthening work motivation can serve as effective strategies to promote extra-role behavior among employees in the hospitality industry.emotional intelligence, employee empowerment, motivation, organizational citizenship behavior, hospitality industry.